ENHANCING BIOGRAPHY WRITING SKILLS THROUGH PROBLEM-BASED LEARNING AMONG GRADE I STUDENTS AT MUARA KATI LAMA ELEMENTARY SCHOOL - Harum Melysa (CV Grasta Glory, 2025)
This research is motivated by the low achievement of students in Indonesian language learning, particularly in writing biographies of historical figures, which requires both linguistic and analytical skills. Many students struggle to organize ideas and express them coherently in writing. This study aims to determine the effectiveness of the Problem-Based Learning (PBL) model in improving biography writing skills among Grade I students at Muara Kati Lama Elementary School. The research was conducted as Classroom Action Research (CAR) involving 16 first-grade students 13 boys and 3 girls. Data were collected through tests, observation, and documentation, and analysed using both descriptive qualitative and quantitative methods. The research was carried out in three cycles, each consisting of planning, implementation, observation, and reflection stages. The results indicate a steady improvement in students’ Indonesian language learning outcomes, particularly in organizing ideas, understanding historical content, and using appropriate language structures in writing biographies. In conclusion, the Problem-Based Learning model effectively enhances students' biography writing skills and can serve as an alternative strategy to improve Indonesian language learning outcomes. Future research could explore the application of PBL in other writing genres or subjects to measure its broader impact. Teachers are encouraged to integrate problem-based approaches with contextual topics to foster student engagement and critical thinking.